Photoelectrochemical hydrogen generation using graded In-content InGaN photoelectrode structures. (May 2019) - Ohkawa, Kazuhiro; Uetake, Yusuke; Velazquez-Rizo, Martin; Iida, Daisuke
Abstract: We have improved the InGaN/GaN heterointerface to achieve higher energy conversion efficiency by replacing a uniform InGaN layer with a graded In-content InGaN layer. Even In0.08 Ga0.92 N/GaN heterostructure has a large conduction band offset, which is large enough to suppress the photocurrent in the photocatalytic system. The graded In-content InGaN structures were grown by metalorganic vapor-phase epitaxy by changing the TMIn flow rate gradually. X-ray reciprocal space mapping confirmed the graded structures. The graded InGaN/GaN structure significantly increased photocurrent and H2 generation by 50% and more compared with the conventional uniform InGaN/GaN structures. Graphical abstract: Image 1 Highlights: High-quality of graded InGaN layers. Investigation of the effect of the graded InGaN on the photochemical phenomena. The graded InGaN layer is no step-like energy barrier in the conduction band. The graded InGaN/GaN structure significantly increased photocurrent and H2 generation.